STRATEGI PROMOSI TEBAR HEWAN KURBAN DOMPET DHUAFA DALAM PERSPEKTIF KOMUNIKASI PEMASARAN TERINTEGRASI - Nenie Sofiyawati (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2023)
Integrated communication channels make it easier for the market to capture promotional messages. Mistakes in designing marketing communication strategies will have an impact on messages that cannot be conveyed. This can damage the company's image because the market cannot find the benefits of the product. This study aims to analyze the promotion strategy of the Dompet Dhuafa Sacrificial Animal Stocking program using the Integrated Marketing Communication (IMC) perspective presented by Philip Kotler and Gary Armstrong. This research applies a qualitative-inductive descriptive method using library data from various relevant sources. The results showed that the promotion of the Dompet Dhuafa Sacrificial Animal Stocking program applies the principles of integrated marketing communication. The IMC principle that emphasizes the integration process of promotional channels that convey one promotional message has been implemented in the promotion of Sacrificial Animal Stocking 1443 H through the message of the benefits of #JadiManfaat sacrifice. All parties involved in THK activities have coordinated their activities on the delivery of sacrificial benefit messages in order to achieve the objectives of the sacrificial decision. The above study can be recommended for managers of institutions that organize sacrificial activities to pay attention to the integration of promotional messages that use various communication channels in order to achieve promotional goals.